Placental treatment with insulin-like growth factor 1 via nanoparticle differentially impacts vascular remodeling factors in guinea pig sub-placenta/decidua - Davenport, Baylea N.; Jones, Helen N.; Wilson, Rebecca L. (Frontiers in Physiology, 2023)
Clinically, fetal growth restriction (FGR) is only detectable in later gestation, despite pathophysiological establishment likely earlier in pregnancy. Additionally, there are no effective in utero treatment options for FGR. We have developed a nanoparticle to deliver human insulin-like 1 growth factor (hIGF-1) in a trophoblast-specific manner which results in increased expression of hIGF-1. IGF-1 signaling in the placenta regulates multiple developmental processes including trophoblast invasion and maternal vascular remodeling, both of which can be diminished in the FGR placenta. We aimed to determine the effects of short-term hIGF-1 nanoparticle treatment on sub-placenta/decidua trophoblast signaling mechanisms in FGR and under normal growth conditions. Using the guinea pig maternal nutrient restriction (MNR) model of FGR, ultrasound-guided, intra-placenta injections of hIGF-1 nanoparticle were performed at gestational day 30-33, and dams sacrificed five days later. Sub-placenta/decidua tissue was separated from placenta for further analyses. Western blot was used to analyze protein expression of ERK/AKT/mTOR signaling proteins (phospho-Erk (pErk), phospho-Akt (pAkt), raptor, rictor and deptor). qPCR was used to analyze gene expression of vascular/remodeling factors (vascular endothelial growth factor (Vegf), placenta growth factor (Pgf), platelet-derived growth factor (Pdgf)) and tight junction/adhesion proteins (claudin 5 (Cldn5), p-glycoprotein (Abcb1), occludin (Ocln) and tight junction protein 1 (Zo1)). MNR reduced expression of pErk, PdgfB and Cldn5, and increased expression of Ocln and Zo1 in the sub-placenta/decidua. In MNR + hIGF1 nanoparticle sub-placenta/decidua, expression of PdgfB, Ocln and Zo1 was normalized, whilst pAkt, VegfB, Vegf receptor 1 and PdgfB receptor were increased compared to MNR. In contrast, hIGF-1 nanoparticle treatment of normal placentas reduced expression of pErk, raptor and increased expression of the mTOR inhibitor deptor. This was associated with reduced expression of VegfA, Plgf, and PdgfB. Here we have shown that the impact of hIGF-1 nanoparticle treatment is dependent on pregnancy environment. Under MNR/FGR, hIGF-1 nanoparticle treatment triggers increased expression of growth factors and normalization of EMT factors. However, under normal conditions, the response of the placenta is to decrease AKT/mTOR signaling and growth factor expression to achieve homeostasis.